The impact of users' age, gender, education, and experience on their satisfaction perception of m-banking app's usability - Mkpojiogu, Emmanuel O.C.; Hashim, Nor Laily (2017)
Purpose - One of the most trending and current technological innovations in mobile commerce today is mobile banking (m-banking).Notably, the ever growing market for mobile phone has led to a consequent parallel mounting opportunities for the growth and saturation of m-banking enterprises with lots of accruing business dividends following.This notwithstanding, the context of use of m-banking apps presents great challenges particularly with regard to mobile usability.The unique features of mobile phones such as smallness of screen size, non-traditional input method among others, make usability complex, hard and difficult and thus, negatively impacts users’ perceived satisfaction and usability of the m-banking apps’ interfaces (Hussain et al., 2015).In the design, service and evaluation of mobile phones, usability is counted as a central issue.This is because users access, and use a range of functions and features in an app through the obviously limited user interface regularly whilst they are on the move (or busy doing other activities).These usability challenges by implication have effect on the users’ perceived satisfaction of mobile banking apps.This paper reports on a study on the perceived satisfaction of users of m-banking apps for three banks in Nigeria.In the study, the impact of users’ age, gender, experience, and education on their satisfaction perception of m-banking apps’ usability was assessed and evaluated.The study was triggered because of the scarcity such studies in available research literature.